2010
DOI: 10.1007/s00265-010-0995-z
|View full text |Cite
|
Sign up to set email alerts
|

Mediating male–male interactions: the role of the UV blue crest coloration in blue tits

Abstract: 18Badges of status, usually color patches, are hypothesised to serve as important 19 signals within natural populations by communicating individual's fighting ability or 20 aggressiveness before an interaction ever takes place. These signals, which may 21 evolve via sexual and/or social selection, mediate intra-specific competition by 22 influencing the outcome or escalation of contests between individuals. The last 10 23 years saw the rise of interest in the role of Ultraviolet (UV)-based coloration in 24 int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 79 publications
2
49
0
Order By: Relevance
“…badges of status) are always shaped by individual social selection. This topic has received much attention in the study of males [42,43,159,223], but our literature review suggests that the same mechanism may be widespread in females. We also note that, unlike sexual selection and mutual social selection, individual social selection can extend beyond species boundaries via interspecific competition [174].…”
Section: Linking Social Contexts and Sexual Patterns Of Ornamentationmentioning
confidence: 96%
“…badges of status) are always shaped by individual social selection. This topic has received much attention in the study of males [42,43,159,223], but our literature review suggests that the same mechanism may be widespread in females. We also note that, unlike sexual selection and mutual social selection, individual social selection can extend beyond species boundaries via interspecific competition [174].…”
Section: Linking Social Contexts and Sexual Patterns Of Ornamentationmentioning
confidence: 96%
“…Each male usually chooses one individual or class of individuals as competitive rivals or mate targets, based, presumably, on genetically encoded rules and/or experiential learning. For example, in some insect species, dominant males preferentially compete with other dominant males in order to optimize energy consumed (Leonard and Hedrick 2009) while in some anuran and avian species, males have been shown to preferentially aggress against subordinate individuals (Arak 1983;Rémy et al 2010). It remains unclear, however, under what circumstances such competitive strategies might change during competitive encounters if environmental or social factors change.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike aggressive behavior in some species of frogs and birds in which males are most likely to attack the weaker males (Arak 1983;Rémy et al 2010), Babina males prefer to vocally compete with resident or dominant rivals. Since female choice is generally the final determinant for mating success (Cox and Le Boeuf 1977;Contreras-Garduño et al 2007), males, in theory, could use dynamic competitive strategies reflecting females' preferences.…”
Section: Male Competitive Strategy Depends On Female Preferencesmentioning
confidence: 99%
“…I found a trend for UV-blue colouration to increase with female age (Figure 4.1), and previous research has found that female tree swallows in their third year of life had significantly less UV-blue colouration compared to older females (Bitton et al 2008). I did not find any relationships between female age and parasitism (see 4.4 Results), however, age (Holberton et al 1990) and UV-blue colouration and brightness (Reudink et al 2009;Remy et al 2010) have been found to be predictors of social status in birds. Therefore female tree swallows with more UV-blue colouration and brighter plumage could be of higher social status and may experience differential costs related to their dominant status.…”
Section: Discussionmentioning
confidence: 93%
“…If, however, more UVblue, brighter plumage is sexually selected in female tree swallows, these females may be experiencing differential costs associated with increased social interactions with potential mates. Furthermore, these females may also be dominant to duller, greener females, as both increased UV-blue colouration and brightness have been found to be associated with higher social status in other species (Reudink et al 2009;Remy et al 2010). More UV-blue, brighter females may therefore engage in an increased number of aggressive interactions if their dominance is repeatedly challenged (Goymann and Wingfield 2004).…”
Section: Discussionmentioning
confidence: 99%